1996
DOI: 10.1111/j.1479-828x.1996.tb03291.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Polypoid Endometriosis‐A Rare Complication Following Withdrawal of Gonadotrophin Releasing Hormone (GnRH) Agonist for Severe Endometriosis: A Case Report

Abstract: A 30-year old female who initially had typical endometriosis treated according to a standard regimen later developed numerous highly vascular endometrial polyps on the vagina, cervix, ureter, serosal surfaces of the uterus, pouch of Douglas (POD) and other areas of pelvic peritoneum as well as the endometrium 8 months after withdrawal of treatment with Zoladex gonadotrophin releasing hormone (GnRH) agonist used for treatment of this disease. We postulate that these polyps developed as a rebound phenomenon upon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 7 publications
1
25
0
Order By: Relevance
“…Compared to literature cases [1][2][3][4][5][6][7][8][9][10][11][12] (Table 1), our case was younger, considerably huge in size, and the lesions developed in the pelvis rapidly as soon as there was a break of hormonal therapy. The cause of this rapid growth of lesions is uncertain, but interruption of hormonal treatment could have contributed to hyperestrinism and raised polypoid masses in this case.…”
Section: Discussionmentioning
confidence: 48%
“…Compared to literature cases [1][2][3][4][5][6][7][8][9][10][11][12] (Table 1), our case was younger, considerably huge in size, and the lesions developed in the pelvis rapidly as soon as there was a break of hormonal therapy. The cause of this rapid growth of lesions is uncertain, but interruption of hormonal treatment could have contributed to hyperestrinism and raised polypoid masses in this case.…”
Section: Discussionmentioning
confidence: 48%
“…This condition has been defi ned as "exophytic or polypoid, tumor-like masses that project from a serosal or mucosal surface or from the lining of an endometriotic cyst." 6 Othman et al 7 reported that these polyps may develop as a rebound phenomenon upon withdrawal of GnRH analogue, as in our case.…”
Section: Discussionmentioning
confidence: 65%
“…Dadmanesh et al , in their series on 15 patients with polypoid endometriosis, also did not report an association with tamoxifen 9. Polypoid endometriosis has also been described in association with withdrawal of gonadotropin-releasing hormone agonist 10. There was no history of tamoxifen or unopposed oestrogen therapy in our case.…”
Section: Discussionmentioning
confidence: 51%